Effect of molar incisor hypomineralization on oral health related quality of life in children and adolescents: a systematic review - Romo Pérez, Camilo (2022)
Introduction: Hypersensitivity, altered dental appearance and fractures are common problems in molar incisor hypomineralization that generate functional and socio-emotional problems. Objective: to evaluate the effect of MIH on oral health-related quality of life in children and adolescents. Materials and methods: A systematic bibliographic search was carried out in electronic databases (Pubmed, Epistemonikos, Dentistry & Oral Sciences Source and Virtual Health Library). Observational studies in English or Spanish conducted between 2016-2022 that evaluated the quality of life of children and adolescents with molar incisor hypomineralization were identified. Results: Of 96 identified studies, thirteen were included in the synthesis. The most frequent diagnostic criterion for hypomineralization of molar incisors was the index of the European Academy of Pediatric Dentistry and nine studies reported the severity of the disease. The most widely used scale to measure quality of life was the Child Perception Questionnaire (CPQ). According to the children's perception, the most affected dimensions were "Oral Symptoms" and "Emotional Well-Being", according to the parents they were "Oral Symptoms" and "Functional Limitations". Girls with molar incisor hypomineralization had worse oral health-related quality of life. Conclusions: The negative effect of molar incisor hypomineralization on children’s oral health-related quality of life seems to vary between the perception of parents and children.